A Restatement of the Satisfaction-Performance Hypothesis - Organ, Dennis W. (Journal of Management, 1988)
This article reviews recent evidence in support of Organ's (1977) argument that satisfaction more generally correlates with organizational prosocial or citizenship-type behaviors than with traditional productivity or in-role performance. An attempt is then made to interpret just what it is in satisfaction measures that provides this correlation, leading to the suggestion that fairness cognitions comprise the major factor. Implications of this interpretation for theory, research, and management practice are offered.